Auxiliary Partial Autologous Liver Transplantation for High-selective Alveolar Echinococcosis: A Proof of Concept. Issue 5 (May 2020) - Aini, Abudusalamu; Shao, Yingmei; Shalayiadang, Paizula; Ran, Bo; Jiang, Tiemin; Zhang, Ruiqing; Aji, Tuerganaili; Wen, Hao
Abstract : Supplemental Digital Content is available in the text.